Avian Bornaviral Ganglioneuritis: Current Debates and Unanswered Questions - Su L. Boatright-Horowitz (Veterinary Medicine International)
Avian bornaviral ganglioneuritis, often referred to as parrot wasting disease, is associated with a newly discovered avian virus from the taxonomic family Bornaviridae. Research regarding the pathogenesis and treatment for this disease is ongoing, with implications for understanding other emerging human and nonhuman diseases, as well as the health and ecology of wildlife. At this time, numerous questions remain unanswered regarding the transmission of the disease, best practices for diagnostic sampling and testing, and whether currently used drug therapies are effective or harmful for afflicted birds. The pathogenesis of the disease also remains unclear with many birds showing resistance to the effects of the virus and being able to remain clinically unaffected for years, while other birds succumb to its effects. New research findings regarding avian bornaviral ganglioneuritis are discussed and important as yet unanswered questions are identified.